MENUMBUHKAN MINAT KEWIRAUSAHAAN MELALUI PEMBUATAN BUSINESS PLAN - Suhermini, Suhermini; Safitri, Teti Anggita (Dinamika Pendidikan, 2010)
The purposes of this research are to generate the interest in entrepreneurship, to improve the motivation to learn entrepreneurship, and to familiarize the students in creating a business plan as a student creativity in developing the character of entrepreneur. The research methods were descriptive analysis with the percentage was 74% and correlation analysis which was used to find out whether any relationship between studentsâ€™ interest in entrepreneurship and creating business plan for Management Department Students of Semarang State University. The result showed Â that there was a significant relationship between interest in entrepreneurship and creating a business plan with significant value was 0032.